2023
DOI: 10.3390/cancers15164148
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of EV-Derived miR-150-5p in Prostate Cancer Metastasis and Its Association with High-Grade Gleason Scores: Implications for Diagnosis

Marian Cruz-Burgos,
Sergio A. Cortés-Ramírez,
Alberto Losada-García
et al.

Abstract: Metastasis remains the leading cause of mortality in prostate cancer patients. The presence of tumor cells in lymph nodes is an established prognostic indicator for several cancer types, such as melanoma, breast, oral, pancreatic, and cervical cancers. Emerging evidence highlights the role of microRNAs enclosed within extracellular vesicles as facilitators of molecular communication between tumors and metastatic sites in the lymph nodes. This study aims to investigate the potential diagnostic utility of EV-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…There are also reports that high levels of miR-19a-3p correlate with low rates of relapse-free survival in patients with PCa, regardless of the Gleason score. According to the report [31], the tumor tissue of patients with locally advanced PCa was cha racterized by a significantly higher level of miR-23b-3p compared to patients with metastatic PCa. The lowest levels of expression of this miRNA were identified in the PCa tissue of patients with metastases in the regional lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports that high levels of miR-19a-3p correlate with low rates of relapse-free survival in patients with PCa, regardless of the Gleason score. According to the report [31], the tumor tissue of patients with locally advanced PCa was cha racterized by a significantly higher level of miR-23b-3p compared to patients with metastatic PCa. The lowest levels of expression of this miRNA were identified in the PCa tissue of patients with metastases in the regional lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular cargo profiling of EVs provides crucial insights into their functional diversity and molecular signatures, allowing for the characterization of EV subtypes and their roles in health and disease. For example, the utility of EV-encapsulated miRNAs was explored as potential diagnostic markers for prostate cancer [ 48 49 ]. By analyzing miRNA profiles in EVs isolated from the blood plasma of both prostate cancer patients and healthy individuals, distinct expression patterns of certain miRNAs such as miR-140-3p, miR-150-5p, and miR-23b-3p were identified in the patient group, demonstrating promising diagnostic accuracy for prostate cancer [ 49 ].…”
Section: B Iomarkers Of Extracellular Vesiclesmentioning
confidence: 99%
“…For example, the utility of EV-encapsulated miRNAs was explored as potential diagnostic markers for prostate cancer [ 48 49 ]. By analyzing miRNA profiles in EVs isolated from the blood plasma of both prostate cancer patients and healthy individuals, distinct expression patterns of certain miRNAs such as miR-140-3p, miR-150-5p, and miR-23b-3p were identified in the patient group, demonstrating promising diagnostic accuracy for prostate cancer [ 49 ]. Research also validated the presence of these EV-associated miRNAs in blood plasma, demonstrating their accurate measurability and highlighting their potential as noninvasive diagnostic and monitoring tools for cancer [ 48 ].…”
Section: B Iomarkers Of Extracellular Vesiclesmentioning
confidence: 99%
“…Canonical intronic miRNAs compared to their adjacent introns are generally spliced at a lower speed. pre-miRNAs move into the miRNA pathway, while other transcripts go through pre-mRNA splicing, producing mature mRNA for protein synthesis [38,62].…”
Section: Mirna Biogenesismentioning
confidence: 99%
“…Nonetheless, the biological mystery of their protection from RNase digestion is unknown. A potential explanation for the mechanisms attributing such protection and invulnerability could be their small length, their binding to protein complexes, as well as the fact that miRNAs are embedded in cell-secreted nanovesicles such as exosomes [36][37][38]. It is shown that within the cancerous microenvironment, tumor-derived vesicles behave as transporters of genetic information, exporting their protein content to tumor-surrounding cells [39,40].…”
Section: Introductionmentioning
confidence: 99%